2016
DOI: 10.1007/s40688-016-0093-y
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Cognitive-Behavioral Therapy for an Adolescent Presenting with ADHD and Explosive Anger: a Case Study

Abstract: This case demonstrates the efficacy of utilizing an intensive, multi-faceted behavioral intervention paradigm. A comprehensive, integrative, school-based service model was applied to address attention deficit hyperactivity disorder symptomology, oppositional behaviors, and explosive anger at the secondary level. The case reviews a multi-modal assessment approach to inform intervention, including a developmental history; parent, teacher, and student interviews; systematic classroom observations; and BASC-2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The second component involved teaching coping techniques, including anger management and relaxation techniques. Parker et al (2016) suggested that anger mediates the relationship between automatic thoughts and harmful behaviors; therefore, we taught children using different cognition models to make them less likely to believe their automatic thoughts. In the last part of the session, children were asked to collaborate and brainstorm to envision their future since research shows that positive psychology provides individuals with positive emotions and social support (Park et al, 2014).…”
Section: Accelerate Cbgt Children's Sessionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second component involved teaching coping techniques, including anger management and relaxation techniques. Parker et al (2016) suggested that anger mediates the relationship between automatic thoughts and harmful behaviors; therefore, we taught children using different cognition models to make them less likely to believe their automatic thoughts. In the last part of the session, children were asked to collaborate and brainstorm to envision their future since research shows that positive psychology provides individuals with positive emotions and social support (Park et al, 2014).…”
Section: Accelerate Cbgt Children's Sessionmentioning
confidence: 99%
“…Researchers have found that school-based cognitive behavioral therapy was effective in treating anxiety dis-orders, depression disorders, ADHD, and obsessive-compulsive disorders (Parker et al, 2016). The possibility that CBT helps to improve cognitive functioning and ADHD symptoms is the reason why we believed that modified CBGT was beneficial to both socially adaptive functioning adolescents with ADHD and impulsivity aggression comorbidity as well as their parents' stress.…”
Section: Introductionmentioning
confidence: 97%
“…Research indicates that one in six children under the age of 17 exhibit behaviors that meet criteria to receive a mental health diagnosis each year (Whitney & Peterson, 2019). In school-aged children and adolescents, attention-deficit/hyperactivity disorder (ADHD), anxiety, and depressive disorders are not only common but are also associated with considerable comorbidity (Parker et al, 2016). Furthermore, research continues to support that the presence of depressive and anxiety disorders significantly increases the overall risk of suicidal behavior in adolescence (Nock et al, 2013; Rohde et al, 1991).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…With the diagnostic intersections of MDD, GAD and ADHD presented in this case, cognitive-behavioral therapy (CBT) was chosen as the foundational therapeutic modality due to numerous empirical supports demonstrating its efficacy (David-Ferdon & Kaslow, 2008; Evans et al, 2014; Higa-McMillan et al, 2016). Research has identified CBT as a psychotherapeutic model to address internalizing and externalizing disorders in youth effectively and is considered efficacious for its use in school settings (Parker et al, 2016; Sulkowski et al, 2012). CBT is a psychotherapeutic model that enables students to understand the connection between their thoughts, emotions, and behaviors.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Researchers have found that school‐based cognitive behavioral therapy was effective in treating anxiety disorders, depression disorders, ADHD, and obsessive‐compulsive disorders (Parker et al, 2016). The possibility that CBT helps to improve cognitive functioning and ADHD symptoms is the reason why we believed that modified CBGT was beneficial to both socially adaptive functioning adolescents with ADHD and impulsivity aggression comorbidity as well as their parents' stress.…”
Section: Introductionmentioning
confidence: 99%